Effect of interventions to reduce wait times for diagnosis and treatment of sleep-disordered breathing in adults: A systematic review. Issue 1 (24th February 2022) - Perry, Sarah; Ronksley, Paul E.; Kelly, Jenny; Pendharkar, Sachin R.
Abstract: RATIONALE: Sleep disordered breathing (SDB) is associated with adverse health consequences that can be mitigated through timely and effective management. Guidelines provide wait time targets, but the evidence supporting them is unclear. The purpose of this systematic review was to explore the relationship between interventions to improve wait times for SDB and the effects on patient or provider outcomes. METHODS: A targeted search of medical databases was performed from database inception to June 2017. Included studies described an intervention intended to reduce wait times for the diagnosis or treatment of SDB and reported on a patient- or provider-level outcome. RESULTS: The search produced 2, 944 abstracts and 51 articles underwent full text review. Ten articles were included in the final review. Five trials reported wait times to diagnosis and treatment, 3 studies described wait times for diagnosis only and 2 studies discussed time to treatment exclusively. All studies were of moderate methodological quality. Wait times were improved in most studies, but due to short follow-up periods a clear relationship with improved health outcomes was rarely established. The variety of interventions limited the characterization of specific wait-times reduction strategies that could reliably improve outcomes. CONCLUSIONS: This review highlights the scarcity of studies but suggests a possible clinical benefit of interventions to reduce wait times. However, generalizability is limited and the short follow-up periods likely underestimate potential positive impacts of reduced wait times. Further studies are needed to better characterize this relationship and to identify additional interventions to deliver more timely patient care.